Clinicopathological Characteristics of Meningiomas: A tricentric Study - Obeidat, Fatima; Al Khader, Ali; Alrjoub, Mo'ath; Al-Mostafa, Sahar; Al Abweh, Ruba; Al-Qaisi, Fatima; Al-Hussaini, Maysa; Tamimi, Ahmad (Jordan Medical Journal, 2025)
Background and Aims: Meningioma is the most common brain tumor in Jordanian adults. This study aimed to analyze the macro- and microscopic features of meningiomas with emphasis on the correlation with tumor recurrence. Materials and Methods: This retrospective study comprised all the meningioma cases diagnosed at three major tertiary care centers in Jordan in 2007-2021. The clinicopathologic data were retrieved from the patients’ records. Results: A total of 690 cases were studied, with the peak age being 45 years. The female-to-male ratio was 2.3:1. Based on the available data for most patients among the cohort, tumor size ranged from 0.5 cm to 11.5 cm, and the most common site was the frontal lobe. The great majority of tumors were grade 1 (80.2%). Male sex was significantly associated with a higher tumor grade and a larger tumor size (p = 0.003 and 0.001, respectively). The 5-year follow up data was retrieved for 206 patients. The recurrence rate was about 28%. Recurrence was significantly associated with tumor size (p = 0.000). The tumor size was also significantly associated with the histologic grade (p = 0.003). Multivariate analysis showed that intracranial tumors were significantly more associated with recurrence than spinal ones (p = 0.017), and that mitotic index was significantly associated with recurrence (p = 0.002). Conclusions: Our results were concordant with international reports. Spinal tumors showed less recurrence rate than intracranial ones, and the mitotic index and tumor size were significantly associated with a higher recurrence rate.